Evaluation of Workloads of Package Deliverers Focusing on Their Pickup and Delivery Tasks in Republic of Korea - Rim, Suk Chul; Jung, Myung Chul (Sustainability (Switzerland), 2022)
Package deliverers are facing increasing workloads due to a rapid increase in online shopping caused by the recent outbreak of COVID-19 in the Republic of Korea. The purpose of this study was to evaluate the physical workload of package deliverers during pickup and delivery tasks. Heart rate reserve (HRR), metabolic equivalent of task (MET), standardized Nordic questionnaire (SNQ), and visual analogue scale (VAS), measured on site using a wristband, were used as indicators of their workload. Twenty deliverers participated in this study. Work analysis was performed to categorize their tasks into sorting inside a truck, delivering, picking up, driving, and resting. Statistical analysis showed that participants spend 4.3 h per day picking up and delivering 331.9 packages per day. Their work requires about 29.7% of HRR and 4.7 of MET, which are thus considered as of “moderate level” difficulty. SNQ and VAS revealed that their lower back and wrist/hand were the most painful body parts due to repetitive trunk bending and small package handling. The use of a cart would be recommended as it has the advantage of handling many packages at once with less physical effort in deliverers.
Keywords: courier service; heart rate reserve; metabolic equivalent of task; standardized Nordic questionnaire; visual analogue scale